Photonic Generation of Flexible and Adjustable Triangular and Square Waveforms Based on a Comparator - Jinjian Feng; Yang Jiang; Jing Xu; Xiaohong Lan; Qianyou Long; Yunkun Luo (IEEE Photonics Journal, 2025)
A photonic approach to generating triangular and square waveforms using a comparator is proposed. Beginning with a sinusoidal waveform, a comparator comprising two Mach-Zehnder modulators converts the sinusoidal waveform into a square waveform with a 50% duty cycle. Through subsequent multiplication, delayed superposition, and integration operations, square waveforms with duty cycles ranging from 20% to 80% and triangular waveforms with symmetry factors ranging from 20% to 80% are achieved. Adjusting the delay enables flexible tuning of both the duty cycle and symmetry factor. Moreover, frequency-doubled waveforms can be generated by modifying the delay. Detailed theoretical analysis is developed, and the experimental results align closely with theoretical predictions, effectively validating the proposed scheme. This approach offers the advantage of flexible adjustment and generates waveforms entirely through time-domain operations, which better preserves the time-domain characteristics of the waveforms and bypasses the complicated consideration of the amplitudes and phases of harmonic components.